A Theory of the Rate of Wages - Hamilton, Walton H. (Quarterly Journal of Economics, 1922)
Other theories of wages deal with other problems than that of raising wages, 581. — Sources from which increase of nominal wages may come, 585. — How may the laborers command a share of these surpluses? 605. — Increasing real wages by lowering the prices of what the laborer buys, 608. — The laborer's free income, 609. — Factors determining a wage rate in a given industry, 610.